QARAQALPAQSTAN PLASTIKALÍQ KÓRKEM ÓNERLERI JÁRDEMINDE STUDENTLERDIŃ KÓRKEM DÓRETIWShILIK QÁBILETI HÁM KÓRKEM TALǴAMÍN RAWAJLANDÍRÍW JOLLARÍ - Urazimova, Tamara Vladimirovna (SCIENCE and SOCIETY, 2026)
The article is devoted to the issues of developing students’ artistic abilities and taste based on the plastic arts of Karakalpakstan. Developing students’ artistic abilities and taste based on plastic art is achieved through practical mastery of painting, sculpture, and graphics, as well as by analyzing their aesthetic information and studying the theoretical foundations of art. This includes developing the skills to perceive and evaluate works of art and forming one’s own creative thinking.